Evaluación de la gestión administrativa del gobierno autónomo descentralizado municipal y su impacto en el desarrollo y crecimiento del cantón la maná, periodo 2010-2011 - Lozada Villagómez, Yolanda Del Pilar (2012)
This research was conducted in the Gobierno Autónomo Descentralizado La Maná, Cotopaxi province, in order to assess the administrative management of the public body and its impact on the development and growth of the community for the 2010-2011 period, for it collection was necessary legal base, and also established indicators of efficiency, effectiveness, economy and ecology to assess the management, to make the diagnosis is known the current situation, in which a report was produced. The population that is applied to 100% of the administrative staff and workers and used a sample of the population of Canton La Maná, taking population data by INEC 2010 is 43,820 inhabitants with a growth of 3.8% per year, which for the purpose of study was obtained in 2011 a sample of 538 inhabitants. According to the analysis of the budget to 85% in 2011 of the works have been completed, which has been found that the decentralized autonomous Municipal Government of La Maná has met with a high percentage of annual planning in relation to the provision of works. According to reports of GAD in 2011, is 88.36% as detailed in the budget is, ie a higher value was given for execution of works with $ 5,318,731.16 in relation to 2010 is 11.64% corresponding to $ 700.939.84, is managing to get background for the works in industry profits improved in 2011. With the study of the administration of Gobierno Autónomo Descentralizado La Maná it was found that their administration is affected in prioritizing their work because they have not taken the steps in due time, which affects the institutional development and citizenship in general. With the reports of the Comptroller General on until June 30, 2010, have been limited to only audit the efforts made by the slaughterhouse and Credit & Collection Titles absent leaving other administrative having GAD. Being immersed in this state in which everyday citizens is heard that this county is not growing rapidly like other cities of Ecuador and the world, the institution's contribution to this practice and theoretical research that has been achieved leave precedential basis to improve the administrative management of the municipal institution which developed this research.